MATHEMATICS LEARNING USING THE TAPPS MODEL BASED ON MIND MAPPING: ITS IMPACT ON STUDENTS' MATHEMATICAL PROBLEM-SOLVING SKILLS : Sumatera Utara, Indonesia - Rizki Aprilia, Nabila; Ulfa Hasanah, Rusi (Jurnal Math-UMB.EDU, 2026)
Students’ mathematical problem-solving skills in Indonesia are still not optimal, so it is necessary to implement a learning model that can train structured thinking and increase student engagement. This study aims to determine the effect and magnitude of the effect of the Mind Mapping-based Thinking Aloud Pair Problem Solving (TAPPS) cooperative learning model on the mathematical problem-solving skills of seventh-grade MTs students in a city in Medan  regarding algebra material. This is a quantitative study using a quasi-experimental method with a pretest–posttest control group design. The research sample consisted of two classes: an experimental class with 28 students and a control class with 28 students. The instrument used was a mathematical problem-solving ability test. Data analysis employed the t-test. Results from the independent samples t-test indicated p < 0.001 < 0.05, thus rejecting H₀. This improvement was indicated by an N-Gain value of 0.36, classified as moderate, and a coefficient of determination R² = 0.372, meaning that students’ mathematical problem-solving skills were influenced by the implementation of this learning model. Thus, the Mind Mapping-based TAPPS model can serve as an alternative approach to mathematics instruction to enhance students’ mathematical problem-solving skills. Keywords: Learning Model; TAPPS; Mind Mapping; Mathematical Problem-Solving Ability